EKSPRESI BAHASA DAN GENDER: SEBUAH KAJIAN SOSIOLINGUISTIK - Munjin Munjin (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
It is difficult to say that the diversity in using a language by men and women is just caused by their sexual difference. Thefact show that the factor of social and culture plays more important role and determines how men and women should speak. There are, atleast, three factors that influence in transforming the difference of language expression, that is, the domination or power, the different way oftreating men or women, and socialization. Because of these factors, we find out some expressions, in English language, which representgender inequalities; e.g., asymmetric marked and unmarked term, and semantical derogation.